Anterior Atlas Fracture After C1 Laminectomy Which Was Successfully Treated by Brace Therapy: A Case Report. Issue 3 (July 2021) - Fujiwara, Yasushi; Harada, Takahiro; Kotaka, Shinji; Ohta, Ryo; Nishimori, Makoto; Adachi, Nobuo
Abstract : Case: We report a case of a 67-year-old male patient who underwent a C1 laminectomy with laminoplasty at C2-3 because of cervical ossification of the posterior longitudinal ligament. At 6 weeks after surgery, neck pain occurred after minor trauma without neurological deterioration. Computed tomography (CT) demonstrated C1 anterior atlas fracture with a 3-mm gap. After a 3-month brace therapy using a Philadelphia collar, the patient's neck pain disappeared with complete bone union according to the CT. Conclusion: Among 14 cases that were reported previously, none of the adult patients achieved bone union by brace therapy. Therefore, this is the only case report in which bone union could be achieved by brace therapy.